Validation of the Vitiligo Noticeability Scale: a patient-reported outcome measure of Vitiligo treatment success - Batchelor, J.M.; Tan, Wei; Tour, S.; Yong, A.; Montgomery, Alan A.; Thomas, K.S. (Wiley, 2016)
Background: Patient-reported outcome measures are rarely used in vitiligo trials. The Vitiligo Noticeability Scale (VNS) is a new patient-reported outcome measure assessing how ‘noticeable’ the vitiligo patches are after treatment. The noticeability of vitiligo after treatment is an important indicator of treatment success from the patient’s perspective.